A non-legally-binding instrument as an alternative to a forest convention - Thomas W. Schneider (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2006)
The question of protecting forests under an international binding convention has challenged nations like few other environmental issues and dominated much of the 'United Nations Conference on Environment and Development' (UNCED) in 1992, where countries ultimately adopted a set of non-legally-binding 'Forest Principles'. The debate among governments intensified UNCED follow-up, in tandem with growing public concern about ongoing deforestation and forest degradation worldwide. In May 2005 the fifth session of the United Nations Forum on Forests (UNFF-5) was held in New York. UNFF-5 was meant to be a milestone for a new chapter of the international forest policy. However, the session ended in complete confusion due to irreconcilable country positions. The session was discontinued without any result. The negotiated Chairmen's text was sent to UNFF-6 (February 2006). The chance to launch a negotiating process on a forest convention was not used. At UNFF-6 it was decided to negotiate at UNFF-7 (April 2007) on a non-legally-binding Instrument (NLBI) on Management, Conservation and Sustainable Development of All Types of Forests (International Instrument on All Types of Forests). A decision to negotiate on a legally-binding-Instrument (LBI) will be subject of the UNFF session in the year 2015.
urn:nbn:de:gbv:253-200912-dk039296-4
Keywords: 630